Liberating literature : feminist fiction in America - Lauret, Maria (Taylor & Francis, 1994)
A bold and revealing book which looks with fresh vision at feminist political writing. Maria Lauret developes a new definition of the genre and illuminates the profound influence and importance of African-American women's writing.